Assessment and Comparison of Molecular Subtyping and Characterization Methods for Salmonella - Tang, Silin; Orsi, Renato H.; Luo, Hao; Ge, Chongtao; Zhang, Guangtao; Baker, Robert C.; Stevenson, Abigail; Wiedmann, Martin (Frontiers in Microbiology, 2019)
The food industry is facing a major transition regarding methods for confirmation, characterization and subtyping of Salmonella. Whole genome sequencing (WGS) is rapidly becoming both the method of choice and the gold standard for Salmonella subtyping, however, routine use of WGS by the food industry is often not feasible due to cost constraints or the need for rapid results. To facilitate selection of subtyping methods by the food industry, we present: i) a comparison between classical serotyping and selected widely used molecular-based subtyping methods including Pulsed-Field Gel Electrophoresis, Multilocus Sequence Typing, and WGS (including WGS-based serovar prediction), and ii) a scoring system to evaluate and compare Salmonella subtyping assays. This literature-based assessment supports the superior discriminatory power of WGS for source tracking and root cause elimination in food safety incident, however, circumstances in which use of other subtyping methods may be warranted were also identified. This review provides practical guidance for the food industry and presents a starting point for further comparative evaluation of Salmonella characterization and subtyping methods.